2022
DOI: 10.1016/j.landusepol.2020.104463
|View full text |Cite
|
Sign up to set email alerts
|

The financialization of rental housing in Tokyo

Abstract: Over the past two decades, the private rental sector has grown significantly in Japan. Once an overlooked sector of the market, it has been seized by the financial industry to the point of becoming the second largest REIT residential market in the world. This paper explores the development of residential REITs in Japan, in a context of demographic decline and urban shrinkage. It highlights the strategies of major Japanese real estate groups to diversify their activities and strengthen their control over popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…Residential REITs seemed to be bound with the office sector, which is consistent with the Tokyo development policy towards becoming a metropolitan city occupied with offices and residential properties (Kamo, 2000). The tenants in residential properties are working people with provision of housing allowance (Aveline-Dubach, 2022), reflecting a stable rental income for the residential property sector. Nonetheless, the findings revealed that these defensive REITs were better for longer-term investment instead of daily investment.…”
Section: Resultsmentioning
confidence: 99%
“…Residential REITs seemed to be bound with the office sector, which is consistent with the Tokyo development policy towards becoming a metropolitan city occupied with offices and residential properties (Kamo, 2000). The tenants in residential properties are working people with provision of housing allowance (Aveline-Dubach, 2022), reflecting a stable rental income for the residential property sector. Nonetheless, the findings revealed that these defensive REITs were better for longer-term investment instead of daily investment.…”
Section: Resultsmentioning
confidence: 99%
“…First, they include the financial market actors involved in capital circulation and securitisation such as private equity funds in rental housing financialisation (Fields and Uffer 2016). Other actors may include those in real estate investment trusts (REITs) (Wijburg 2019;Aveline-Dubach 2020). Financial capital drives the process of financialisation through operating financial circulation.…”
Section: The Financial Turnmentioning
confidence: 99%
“…Building on studies such as those by Aveline‐Dubach (2014, 2020) and Aveline‐Dubach et al (2014) regarding the effects of transit‐oriented development models on locational choices for new condominium construction that focused on the case of Tokyo, the hypothesis of the present study was that “with the progress of UCR in Osaka City, condominium construction in the urban centre is gradually changing to locations with high accessibility to public transportation.” To test this hypothesis, I first identified appropriate cases for analysis in Osaka City.…”
Section: Introductionmentioning
confidence: 99%